Extending the age range for breast screening in England: pilot study to assess the feasibility and acceptability of randomization. - Moser, K; Sellars, S; Wheaton, M; Cooke, J; Duncan, A; Maxwell, A; Michell, M; Wilson, M; Beral, V; Peto, R; Richards, M; Patnick, J (2011)
OBJECTIVE: To assess the feasibility and acceptability of randomizing the phased introduction of the extension of the invited age range in the National Health Service (NHS) Breast Screening Programme in England from 50-70 to 47-73 years. SETTING: Six volunteer breast screening units (BSUs) in England. METHODS: Cluster-randomized trial of invitation versus no invitation for breast screening. STUDY PARTICIPANTS: women aged 47-49 and 71-73 years in screening batches randomized between 1 June 2009 and 31 May 2010. OUTCOMES: workload, screening uptake among women invited, self-referrals among women not invited, and screening outcomes among women invited. RESULTS: A total of 312 screening batches (clusters) were randomized including 60,708 women. Screening uptake was 63% in women aged 47-49 and 62% in women aged 71-73. Those who attended screening in the younger age group were more likely to be recalled for assessment than older attendees (7.5% vs. 3.0%) but less likely to be diagnosed with breast cancer (0.5% vs. 1.1%). Among women not invited, 0.2% of those aged 47-49 and 6.8% of those aged 71-73 self-referred for screening. Despite the extra workload BSUs largely coped although there was some slippage in round lengths and other targets. CONCLUSION: No major problems of feasibility or acceptability of randomization were found. This pilot study has informed the randomized phasing-in of the age extension across the whole of England.